Manajemen Konflik Suami Terhadap Istri Nusyuz Dalam Perspektif Hukum Islam Di Nagari Talang - Friska Delia; M Hidayat Ediz; Isnadul Hamdi (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2026)
This study reveals how husbands in Nagari Talang respond to their wives' nusyuz. Through descriptive analysis of the Miles and Huberman model based on Islamic law and Thomas-Kilman, the findings of this phenomenological study indicate that husbands' conflict resolution practices typically follow the steps outlined in Surah An-Nisa verse 34, which include separating beds (hajr), providing persuasive advice (mau'izhah), and mediation efforts that often involve the role of Ninik Mamak as customary authorities to maintain family dignity. The husband's level of religious knowledge and structural support from local conventions have a significant impact on how well these stages are handled, even when they are in accordance with Islamic law.